2021
DOI: 10.3389/fphar.2021.651582
|View full text |Cite
|
Sign up to set email alerts
|

Folate Reverses NF-κB p65/Rela/IL-6 Level Induced by Hyperhomocysteinemia in Spontaneously Hypertensive Rats

Abstract: Hyperhomocysteinemia (HHcy) is derived from the abnormal metabolism of homocysteine (Hcy) and is related to metabolic-related diseases. In addition, HHcy combined with hypertension increases the risk of cardiovascular diseases (CVD). However, the mechanism of HHcy aggravating hypertensive arterial damage and the efficacy of folate (FA) as a beneficial supplement have not been fully elucidated. In this study, we established a rat HHcy model and a hypertension combined with HHcy model. Rat tail artery blood pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Studies found that HHcy can significantly increase cardiovascular and cerebrovascular events in hypertension 5 . Another study found that the levels of oxidative stress and inflammation are increased in hypertension associated with HHcy 6 . However, the molecular mechanism of HHcy synergistically aggravating the arterial damage in hypertension is rarely reported.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Studies found that HHcy can significantly increase cardiovascular and cerebrovascular events in hypertension 5 . Another study found that the levels of oxidative stress and inflammation are increased in hypertension associated with HHcy 6 . However, the molecular mechanism of HHcy synergistically aggravating the arterial damage in hypertension is rarely reported.…”
Section: Introductionmentioning
confidence: 97%
“…study demonstrated that Nox is involved in the target organ damage of hypertension and HHcy-induced oxidative stress 6 . However, it is unclear whether oxidative stress is the leading cause for arterial pathological changes of hypertension associated with HHcy, and whether HHcy aggravates the arterial damage of hypertension through Nox2 or Nox4 signaling pathways.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…Plasma Hcy levels of 10 or more μmol/L were considered to indicate H-type hypertension in China’s “H-type hypertension diagnosis and therapy of expert consensus” in 2016. HHcy up-regulates the expression of interleukin-6 (IL-6) and nuclear factor-κB (NF-κB) p65/Rela, induces oxidative stress and inflammation, and leads to hypertension [ 15 ]. Boachie et al found that low vitamin B12 levels can increase metabolic disorders and induce hypertension by affecting epigenetic mechanisms, such as DNA methylation, histone modifications and micro-RNA [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…4 It is well known that folic acid (FA) can alleviate HHcy. 5 Folic acid is one of the essential vitamins of the human body, and participates in the coenzyme of many human enzymes. 6 Folic acid is also an important antioxidant in the body.…”
Section: Introductionmentioning
confidence: 99%